Correlation between Content of Collagen I and Tenascin-C Sacrouterine Ligament in the Uterine Prolapse - Aditya Mulyakusumah (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: To analyze differences in mean and correlation between content of collagen I and tenascin-C sacrouterine ligaments in patients with uterine prolapse. Method: This type of research is analytic comparative and cross sectional correlation is cut in two research groups. Well conditioned paraffin block of patients uterine prolapse and without uterine prolapse were stained with immunohistochemical staining. The preparation is examined under a light microscope by the Pathology Specialist, assessment of content is done by looking at the distribution and intensity of the color of collagen fibers and tenascin-C. Result: There were significant mean differences between the content of collagen I and tenascin-C sacrouterine ligament in patients with uterine prolapse and without uterine prolapse (p = 0.001). There was no correlation between the content of collagen I and tenascin-C sacrouterine ligament in patients with uterine prolapse (p = 0.780). Conclusion: There was a difference in the average content of collagen I and tenascin-C in the uterine prolapse group compared with no uterine prolapse group. There was no correlation betweenthe content of collagen I and tenascin-C in the uterine prolapse group. [Indones J Obstet Gynecol 2011; 35-4:186-90] Keywords: collagen I, tenascin-C, sacrouterine ligament, uterine prolapse